Clearing the Plains and Teaching the Dark Side of Canadian History - Neylan, Susan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2015)
James Daschuk’s Clearing the Plains is a fitting choice for unsettling national narratives about the peaceful resettlement of Indigenous homelands, for confronting presumptions about the benevolence of Canadian policy towards Indigenous peoples or a fair treaty process, and for appreciating how this past resonates today. This paper ponders how the book and the issues it raises can be used in university-level teaching. It highlights the utility of an emphasis on the “dark” side of Canadian history and how this fits within contemporary discussions around reconciliation.